Single-Quantum-Dot Heat Valve - B. Dutta; D. Majidi; N. W. Talarico; N. Lo Gullo; H. Courtois; C. B. Winkelmann (AMER PHYSICAL SOC, 2022)
We demonstrate gate control of electronic heat flow in a thermally biased single-quantum-dot junction. Electron temperature maps taken in the immediate vicinity of the junction, as a function of the gate and bias voltages applied to the device, reveal clearly defined Coulomb diamond patterns that indicate a maximum heat transfer at the charge degeneracy point. The nontrivial bias and gate dependence of this heat valve results from the quantum nature of the dot at the heart of device and its strong coupling to leads.